Induction of Apoptosis of Cancer Cells Using the Cisplatin Delivery Based Electrospray (CDES) System - Myung Chul Lee; Shambhavi Pandey; Jae Woon Lim; Sangbae Park; Jae Eun Kim; Hyunmok Son; Jinsub Han; Hoon Seonwoo; Pankaj Garg; Jong Hoon Chung (Applied Sciences, 2021)
Cisplatin, a representative anticancer drug used to treat cancer, has many adverse effects. In particular, it causes significant damage to the kidneys. Thus, many researchers have studied the delivery of drugs, such as cisplatin, to cancer areas using targeted drug-delivery systems. Here, we propose a new way to treat cancer by delivering anticancer drugs directly to the tumor site using the electrospray (ES) technique. We determined the optimal conditions for ES to promote the introduction of cisplatin into cancer cells. In our results, the group with cisplatin delivery-based electrospray (CDES) at 6 kV had an apoptosis of cancer cells approximately two times more than the group treated with cisplatin alone. We also confirmed that ES alone did not affect the survival of cells up to a voltage of 6 kV, but increased the permeability of the cell plasma membrane instantaneously, facilitating the influx of the drug.